A simplified transport model for the ex ante evaluation of road pricing on a project basis. Issue 4 (4th October 2017) - Kopsacheili, Angeliki; Pnevmatikou, Anastasia; Yannis, George; Diamandouros, Konstandinos
Abstract : The objective of this research is the development of a diversion transport model that adopts a specific technique for forecasting changes in demand when examining road pricing schemes for two generic types of road projects: a new road project and the upgrade of an existing roadway. It is assumed that the key drivers of demand are roadway capacity and generalised cost of travel. The model incorporates most of the transport behaviours and sensitivity desired in a transport model, yet it has a simple structure (sketch-based model) and manageable data requirements. Due to its simple structure, the model is developed for use mainly by public authorities, with limited resources or know-how in transport modelling. The model was applied in order to produce a (defensible) simulation of the 'immediate' impacts of road pricing policies (traffic volume, amount of travel, journey time, speed, etc.) on given road projects. Model results were used for the estimation of traffic-related impacts that are usually included in an ex ante evaluation of a road project (reduction of traffic congestion, improvement of safety level, improvement of air quality and reduction of noise annoyance).